Eco-revelatory design of proposed Ganano Waterfalls development in Baguio Village, Diffun, Quirino - Inieto, Samantha F.; Villajuan, Jose Dan (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
The Philippines being an archipelago is endowed and known for its beaches and marine wonders. But more than its palm-dotted attractions are an array of waterfalls varying in height, width and natural pools tucked inside the country’s forests. While only several waterfalls may be regarded as tourism destinations, many are attractions. Often associated with ecotourism, waterfalls help to diversify the tourism product and spread the benefits as well as some of the associated problems of tourism to less developed areas.
This study empirically makes use of the theoretical proposition of eco-revelatory landscape design - a design theory in which the physical revelation of ecological processes and relationships in an area encourages the users of that particular landscape to value those ecological processes. As a part of the Quirino Protected Landscape (QPL), the Ganano Falls in Baguio Village, Diffun, Quirino is set into the goal of conserving thefull range of its biodiversity towards ecotourism activity in a manner by which can be realized. The final output for this study is a site development plan for the area.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Ecology -- Quirino; Waterfalls -- Quirino; Ganano Waterfalls (Quirino)